Stress Induced by Simulated Nitric and Sulphuric Acid Rain on the Nutrient Quality of Cucurbita moschata (Duchesne ex Poir) (Global Journal of Science Frontier Research, 2018)
Stress has been associated with several alterations in the physiological and biochemical composition of plants affecting their use in chemotherapy. Investigations were carried out to assess simulated nitric acid rain (SNAR) and simulated sulphuric acid rain (SSAR) stress on the medicinal quality of Cucurbita moschata. Results revealed that all the nutrients investigated had higher values at pH 6.0 than at pH 2.0, 3.0 and 4.0. The presence or absence of phytochemicals was not affected by SNAR and SSAR levels. Stress induced on ash, fat, fibre, carbohydrate and moisture caused significant (P=0.05) increase at pH 2.0 and 3.0 with decrease at pH 4.0 with the exception of leaf protein which showed increase at all levels of acidity compared to the control pH 6.0. Amino acids depicted a trend similar to that of protein. Potassium, sodium, calcium, magnesium, iron, copper, zinc, manganese and P were seriously affected by simulated acid rain stress. Stress caused an increase in vitamin A and the B-complex vitamins at pH concentration 2.0 with a decrease at concentration 3.0 and 4.0. While vitamin C was significantly reduced by simulated acid rain stress, vitamin K showed increase in content at all levels of acidity.
Keywords: cucurbita moschata; medicinal quality; stress; simulated nitric and sulphuric acid rain